The 18th-Century Ottoman Scholar Hafîd al-Nitharî’s Treatise on the Createdness of al-Māhiyāt: An Examination and Critical Edition - Murat Kaş (İslam Tetkikleri Dergisi)
Avicenna’s metaphysical comprehension of the distinction between essence and existence is not just a step towards grounding the necessary existent (i.e., God), but also has the intention of providing an explanation of the relation between the necessary and contingent existents and the createdness of the latter. Fakhr al-Dīn alRāzī’s (d. 606/1210) critical reading of Avicenna (d. 428/1037) through the status of quiddity in itself, the causes of existence and essence, existentialism of things, and how related matters make the createdness of quiddity/essence is a problematic case in philosophical theology. If the createdness of contingent things is a non-controversial issue among all the schools of Islamic philosophy, kalam, and theosophy, the question of what makes this topic debatable becomes a starting point for analyzing the positions and arguments related to this discussion. Some scholars who’ve tackled the problem with regard to the meaning of create (ca´l) and quiddity (māhiya) contend that opposing views had arisen from the different meanings assigned to these terms. According to the viewpoints of these scholars, the debate is not philosophical in itself, but rather philological. According to some scholars, however, the problem should not be reduced to philological analyses as it has significant implications and is connected to important philosophical issues. If it wasn’t, the assertion that it has only a philological nature would imply that the participants in the discussion had no idea what they were talking about and would mean that they maintained a sterile discussion. This article contains an evaluation of the Ottoman Hanafite-Māturidite scholar Hafīd al-Nithārī’s (d. 1188/1774) treatise and critical edition on the createdness of quiddity in the previously mentioned context.